X-Ray Diffraction Pattern of the Complex of Heptasulfaimide with Sn(IV) - Tripathi, U.K.; Jadon, S.P.S. (Asian Journal of Chemistry, 2016)
On refluxing SnI4 with S7NH, Sn4+ is reduced to Sn2+ with the formation of (S7N)2·SnI2 as confirmed by its mass and IR spectra. The values of axial ratios and axial angles determined from its XRD pattern suggest monoclinic packing of its unit lattice.